(untitled) (Journal of Engineering, 2018)
An experimental investigation has been carried out for zinc-nickel (Zn-Ni) electro-deposition using the constant applied current technique. Weight difference approach method was used to determine the cathode current efficiency and deposit thickness. Also, the influence effect of current density on the deposition process, solderability, and porosity of the plating layer in microelectronic applications were examined. The bath temperature effect on nickel composition and the form of the contract was studied using Scanning Electron Microscope (SEM). Moreover, elemental nature of the deposition was analyzed by Energy Dispersive X-Ray (EDX). It has been found that the best bath temperature was 40˚C, specifically at a concentration of 73 g/L of NiCl2.6H2O, has a milestone influence on the nickel composition and structure of the deposits. The potential is a major factor influencing the deposition coating alloy which is adjusted by the operations of the cathodic polarization; rather than the standard potential of the two metals as determined by the e.m.f. series. The anomalous deposition was obtained at a current density lower than 0.8 A/dm2, while normal deposition occurred at current densities less than 1.2 A/dm2. Corrosion behavior was exhibited by the bath and for performance was carried out, and it shows that the best corrosion performance was for nickel composition of 10-12.6 wt%.